Prognosis in colorectal cancer beyond TNM - Neves,Ana Lídia Ferreira (2020)
ABSTRACT Introduction: Colorectal cancer is one of the neoplasms with the greatest social impact. Given the great molecular heterogeneity and diversity of pathophysiological mechanisms, it is difficult to define prognostic factors that could guide therapy. Objectives: To identify the molecular prognostic factors that may be of interest in clinical practice and to synthesize the existing evidence. Material and methods: The search for the articles was carried out using the PubMed platform and the keywords “sporadic colorectal cancer and prognosis”, for articles published between 2014 and 2019. We selected all articles published on studies in humans and written in English or Portuguese. Of the 215 articles found, 35 articles were selected to perform this review. Results: Current evidence supports the use of four molecular markers in clinical practice − KRAS, NRAS and BRAF (EGFR signalling pathway) and the mismatch repair status. Conclusion: The use of molecular biomarkers in clinical practice to define prognosis is still little supported by the existent evidence. The studies are slightly contradictory, so new projects and international collaborations must be carried out in this area to obtain more robust evidence.